Studies on The Divine Comedy by Józef Ignacy Kraszewski and the Beginnings of Polish Dante Studies (1820–1870) - De Carlo, Andrea F. (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article analyses Józef Ignacy Kraszewski’s contribution to the development of Polish Dante studies – thanks to his lectures on Dante held in Krakow and Lviv in 1867 and later published under the title Studies on The Divine Comedy, 1869. The article presents other opinions of Dante scholars of the time and more or less critical reviews of the results of Kraszewski’s research.